Vertebrate Conservation and Biodiversity - Hawksworth, David L.; Bull, Alan T. (Topics in Biodiversity and Conservation, 2007)
This book brings together a selection of original studies submitted to Biodiversity and Conservation that address the conservation and biodiversity of vertebrates - particularly those in terrestrial habitats. Vertebrates are, along with plants, the best-known and most intensively studied components of biological diversity on Earth. While studies on vertebrates can be expected to provide models for other groups, they can also pose their own particular problems due to their relative mobility as in some migratory birds. In addition, many mammals and fish are also subject to extensive human exploitation for food or sport. The contributions in this volume are drawn from a wide range of countries - from Australasia, East Africa, Europe, and North, Central and South America. Collectively they provide a snap-shot of the types of studies and actions being taken in vertebrate conservation - topical examples that will make the volume especially valuable for use in conservation biology courses. Reprinted from Biodiversity and Conservation, volume 16:4 (2007).